2019
DOI: 10.3390/su11071893
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effects of Economic Agglomeration on Haze Pollution in Yangtze River Delta China Using an Econometric Analysis

Abstract: Haze pollution, a serious livelihood and environmental issue, has hindered China’s economic development. This paper, based on the improved output density model, empirically analyzes spatial patterns and impact factors of haze pollution within the Yangtze River Delta from 2015 to 2017 by statistical and spatial econometric models. The study shows that: (1) The characteristics of haze pollution due to seasonal changes are obvious in the Yangtze River Delta region, and the situation has gradually improved. (2) Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…All these cases demonstrate that there is only one positive zero point of (27), indicating that if g > 0, the effect of agglomeration on haze pollution is always positive before the certain positive zero point and negative after it. More specifically, the relationship between agglomeration and haze pollution is in an inverted-U shape, and the corresponding mechanisms are: first, agglomeration stimulates innovation, and innovation can reduce the haze pollution of this economy; second, through innovation, agglomeration also promotes economic growth, and economic growth causes more pollutant emissions and aggravates the haze pollution problem.…”
Section: Equilibriummentioning
confidence: 93%
See 3 more Smart Citations
“…All these cases demonstrate that there is only one positive zero point of (27), indicating that if g > 0, the effect of agglomeration on haze pollution is always positive before the certain positive zero point and negative after it. More specifically, the relationship between agglomeration and haze pollution is in an inverted-U shape, and the corresponding mechanisms are: first, agglomeration stimulates innovation, and innovation can reduce the haze pollution of this economy; second, through innovation, agglomeration also promotes economic growth, and economic growth causes more pollutant emissions and aggravates the haze pollution problem.…”
Section: Equilibriummentioning
confidence: 93%
“…In general, the Cobb-Douglas function α represents the share of the income of labor, and a number of studies suggest that it is between 60% and 70% in China (e.g., Fève et al set α = 2/3 [35]). Thus, the coefficient of the square term (1-2α)λ/α < 0, which means function (27), is in an inverted-U shape. If g = 0, function (27) equals ρθδL, which is greater than zero, indicating that the intercept of this quadratic function is positive.…”
Section: Equilibriummentioning
confidence: 99%
See 2 more Smart Citations
“…Yan et al 16 , analyzed the temporal and spatial evolution characteristics of PM 2.5 in Jing-Jin-Ji, and found that PM 2.5 pollution in Jing-Jin-Ji area has significant spatial spillover effects. Ma et al 17 , studied the spatial characteristics of haze pollution in the Yangtze River Economic Belt and found a positive spatial correlation and significant spillover effect of haze pollution. In addition, there were many literatures that use spatial econometric model to analyze the spillover effect of haze pollution 18,19 .…”
Section: Spatial Association Effect Of Haze Pollution In Cheng-yu Urbmentioning
confidence: 99%